The Effective Strategies for Developing Religious Character Based on School Culture: The Perspectives of Thomas Lickona and Glock & Stark - Zeki Yusuf; Khozin; Pradana Boy Zulian (Universitas Muhammadiyah Malang, 2024)
This research used a qualitative approach with the type of field research that aims to uncover the strategy of religious character formation applied at SMK Muhammadiyah Lumajang. The background of this research includes two main things: first, vocational school graduates are orientated to the world of work so that good character is an absolute requirement; Second, significant school achievements compared to similar schools that have been established for a long time. The results of the study show that the strategy of forming religious character in SMK Muhammadiyah Lumajang has developed into a school culture through several approaches. The exemplary approach is the main focus, where the principal and teaching staff play a role model in daily behavior, demonstrating the importance of religious principles in real practice to shape the character of students. In addition, instilling discipline through strict rules related to punctuality and regularity is expected to create a conducive environment for learning and character growth. Positive habits through activities such as duha prayers, recitations, community service, and other religious activities become an important foundation, teaching students to internalize religious values in daily life. Conditioning of a comfortable, clean, and orderly school environment helps create an atmosphere conducive to student learning and development, supported by good physical facilities and supportive policies. Finally, the integration and internalization of religious values in all school activities is an important step in the formation of students' religious character by uniting the school's vision and mission with religious principles to create a holistic school culture and support the development of students' character in spiritual, moral, and social aspects.